Effectiveness and tolerability of different therapies in preventive treatment of MOG-IgG-associated disorder: A network meta-analysis - Wang, Xiaofei; Kong, Lingyao; Zhao, Zhengyang; Shi, Ziyan; Chen, Hongxi; Lang, Yanlin; Lin, Xue; Du, Qin; Zhou, Hongyu (Frontiers in Immunology, 2022)
Background: Immunotherapy has been shown to reduce relapses in patients with myelin oligodendrocyte glycoprotein antibody-associated disorder (MOG-AD); however, the superiority of specific treatments remains unclear. AIM: To identify the efficacy and tolerability of different treatments for MOG-AD. Methods: Systematic search in Pubmed, Embase, Web of Science, and Cochrane Library databases from inception to March 1, 2021 were performed. Published articles including patients with MOG-AD and reporting the efficacy or tolerability of two or more types of treatment in preventing relapses were included. Reported outcomes including incidence of relapse, annualized relapse rate (ARR), and side effects were extracted. Network meta-analysis with a random-effect model within a Bayesian framework was conducted. Between group comparisons were estimated using Odds ratio (OR) or mean difference (MD) with 95% credible intervals (CrI). Results: Twelve studies that compared the efficacy of 10 different treatments in preventing MOG-AD relapse, including 735 patients, were analyzed. In terms of incidence of relapse, intravenous immunoglobulins (IVIG), oral corticosteroids (OC), mycophenolate mofetil (MMF), azathioprine (AZA), and rituximab (RTX) were all significantly more effective than no treatment (ORs ranged from 0.075 to 0.34). On the contrary, disease-modifying therapy (DMT) (OR=1.3, 95% CrI: 0.31 to 5.0) and tacrolimus (TAC) (OR=5.9, 95% CrI: 0.19 to 310) would increase the incidence of relapse. Compared with DMT, IVIG significantly reduced the ARR (MD=−0.85, 95% CrI: −1.7 to −0.098). AZA, MMF, OC and RTX showed a trend to decrease ARR, but those results did not reach significant differences. The combined results for relapse rate and adverse events, as well as ARR and adverse events showed that IVIG and OC were the most effective and tolerable therapies. Conclusions: Whilst DMT should be avoided, IVIG and OC may be suited as first-line therapies for patients with MOG-AD. RTX, MMF, and AZA present suitable alternatives.